Unleashing the Power of CSS advanced techniques for responsive user interfaces. - Eckles, Stephanie (SitePoint, 2023)
Many new and improved features have landed in CSS over the past few years, and a cross- browser effort to improve compatibility has made the language more stable than ever! The coordinated implementation of new features across browsers these days means we can start to use these features pretty much as soon as they appear, which is great for keeping our stylesheets as simple as possible. A few, single-line properties can now replace multi-line, hacky solutions. In some cases, newly available features may even mean we can remove JavaScript workarounds we once needed to get around old limitations! In this tutorial, we'll review these enhancements to layout, responsive design, element styling, properties, and selectors, and also peek at upcoming features; we'll take a deep-dive into using the CSS :has() selector for scaling reusable components; discover the practical uses of container queries; and also learn how to create responsive CSS layouts without using media queries.